All-on-Four Rehabilitation: A Systematic Review of Clinical Management, Workflow and Complications - Benjamin Reto Huber; Noah Walser; Thiemo Gamma; Philipp Metzler (Dentistry Journal, 2026)
Background: Severe tooth loss affects approximately 267 million people worldwide and has a significant impact on quality of life and general health. Various prosthetic treatment concepts exist for oral rehabilitation. The All-on-Four concept, first described by Maló in 2003, is considered a modern approach for timely and patient-friendly restoration of oral function and esthetics. Methods: A systematic literature search was conducted in the electronic databases MEDLINE/PubMed and EMBASE (Elsevier). Eligible studies were identified according to the framework, including investigations on the All-on-Four concept (PIO) and alternative implant-supported full-arch rehabilitation strategies (FDP4+, PCO). The methodological quality of the included studies was assessed using the Newcastle–Ottawa Scale. Results: Following the selection process, eleven PIO studies and nine PCO studies were included for qualitative analysis. Reported prosthesis survival rates were comparable between All-on-Four (85.0–100%) and concepts with more than four implants (88.2–100%) over up to 20 years. Implant survival ranged from 89.7–97.9% for All-on-Four and 98.9–99.0% for alternative concepts. Marginal bone loss after 5 years reached up to 1.9 mm for All-on-Four and 2.9 mm for alternative concepts. Metal–ceramic prostheses demonstrated lower fracture rates (7.27–18.2%) compared with metal–acrylic restorations (7.3–36.7%). Discussion: The available evidence suggests that the All-on-Four concept represents a predictable treatment option for edentulous patients, with implant and prosthetic survival rates comparable to FDP4+ concepts. Immediate loading protocols may improve patient satisfaction and reduce treatment time when adequate primary stability is achieved. However, biological and technical complications remain clinically relevant. Interpretation of the findings is limited by heterogeneous study designs and predominantly retrospective evidence. Conclusions: The All-on-Four concept provides a reliable rehabilitation option for patients with advanced ridge atrophy who decline regenerative procedures or removable prostheses. Current evidence indicates no significant differences in survival or complication rates compared to other implant-supported treatment concepts.